Challenges Social Work Students Encounter in International Field Placements and Recommendations for Responsible Management - Matthew, Lenore E.; Lough, Benjamin J. (Journal of social work education, 2017)
Social work students often face personal and institutional challenges prior to, during, and after international field placements. If not managed, these challenges may compromise students' professional development and hinder their meaningful contribution to placements abroad, which is of particular concern when students from the Global North are placed in the Global South where uncontested ethnocentrism may exacerbate postcolonial power dynamics. In this article, we evaluate current social work literature on international field placements and set forth challenges that students commonly encounter. Of 24 previous studies we review, four personal and five institutional challenges are identified and assessed. We then recommend five actions to manage these challenges and suggest implications for schools of social work.